The Culture of War in the Pre-Islamic Arab Tribal Mentality: A Study of its Causes and Goals (Raparin Journal of Humanities (RJH), 2025)
This study focuses on the culture of aggression, rape, attack and plunder of pre-Islamic Arab tribes, which was a common tradition of pre-Islamic Arab tribal society, a return to its origins and Tribal conflicts, by explaining the causes and objectives. The tribes of the Arabian Peninsula had often been at war with each other which had been part of their tribal law, characterized by tribal racism; a sign of their success in desert life that was most important. Most tribal relations at that time were organized on the basis of hostility, or alliances and treaties based on mutual assistance.What distinguishes Arab life in pre-Islamic times was their aggressive life, which had become part of the tribal culture. The foundations of the society were based on force and bloodshed. The importance of this subject and its impact on the history of tribal conflict and their future, of course, deserves special research, all these characteristics were the reason for us to choose that topic to shed light on.The research consists of two main trends. In the first trend, the reasons for the outbreak of Arab tribal warfare before Islam were explained. In the second trend, we discuss the most important goals of the war. Finally, the results and the list of references were presented.